Analisis Pengaruh Influencer dan EWOM terhadap Minat Beli Skincare pada Generasi Z di Kota Batam: Peran Mediasi Brand Image - Nurjanah, Listia; Limanda, Kelfi Yanti (Jurnal Manajemen Bisnis dan Keuangan, 2024)
Rapid developments in the skincare industry have created increasingly fierce competition and require the development of effective marketing strategies. In this context, influencers are one of the strategies adopted to support marketing efforts in the industry. Therefore, this research aims to evaluate the main factors influencing Generation Z's buying interest in skincare products in Batam City. Data was collected through a questionnaire distributed to Generation Z, which is interested in skincare products as research objects and has 321 respondents. The data analysis method used is SmartPLS 3.0, with a quantitative analysis approach. The research results show that influencers who meet the criteria of attractiveness, expertise, social media influence, and EWOM influence the image of skincare brands. The image of the skincare brand also significantly influences Generation Z's buying interest in Batam City. The mediating role of brand image influences attractiveness, expertise, social media influence, and EWOM on purchase intention. However, there is a criterion for influencers, namely trustworthiness, which does not significantly influence the skincare brand's image. Apart from that, the role of skincare brand image does not influence trustworthiness on purchase intention.